Identifikasi Cedera dan Kondisi Fisik pada Atlet Hockey Indoor Kota Semarang Tahun 2023 - Rival Nur Ihsan (Indonesian Journal of Kinanthropology (IJOK), 2024)
Background: Hockey athletes require components of the physical condition of speed, agility and endurance in the game. Causes of injury in hockey games include collisions with opponents or teammates, collisions with balls, collisions with sticks, and not using standard equipment to play hockey such as gloves, shin guards and face masks. This study aims to determine the injuries experienced by indoor hockey athletes in Semarang City in 2023 and to determine the physical condition of indoor hockey athletes in Semarang City in 2023. Methods: survey test with a questionnaire and a physical condition test. Data analysis techniques used descriptive statistics with data presentation in the form of tables with percentage calculations and criteria. Results: The results obtained were that the types of injuries often experienced by indoor hockey athletes in Semarang City were bruises and abrasions and the strength component was in the good category, the agility component was in the good category, the speed component was in the poor category, and the endurance component was belong to the less category. The physical condition component of indoor hockey athletes in Semarang City is in the moderate category. Conclusions: The conclusion of this study is that the types of injuries that are often experienced by indoor hockey athletes in Semarang City are bruises and abrasions and the physical condition of indoor hockey athletes in Semarang City is in the moderate category